If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4z-6z=18
We move all terms to the left:
4z-6z-(18)=0
We add all the numbers together, and all the variables
-2z-18=0
We move all terms containing z to the left, all other terms to the right
-2z=18
z=18/-2
z=-9
| 8−f=–12−8f+7f | | c/2−4=6 | | x(9x-10)=(3x-2)(3x-2) | | x+5*(x-6)=4*(x-1) | | 166=114-y | | 188=288-x | | -3-2t=7-4t | | 136-y=250 | | 2x+5(-4-5x)=-158 | | 3p+4=43 | | -x+221=169 | | 4g+116=180 | | 93=-3(4-5x) | | -6+2d=4d | | y+4/9=2/3 | | 2p-3=23 | | 8.5x-3(2x+8)= | | 2p-3=21 | | 2y=y+64 | | 6h=180 | | 12=3(4+m) | | 3(m+6)=27 | | 49s^2-14=0 | | (2x+7)(3x+-8)=0 | | 5/4x-3=-1/2x+4 | | 29x-1=28 | | 7x2-3x-16=0 | | 0.1x=25(200)+.05x | | (2x+8)-115-118-81=x | | 9a−a−7a=5 | | 2d+83=1312d | | -8=x/16 |